Beneficial role of broccoli and its active ingredient, sulforaphane in the treatment of diabetes - Aminu Mohammed; Hafsat Abdullahi Mohammed (Elsevier, 2023)
Background: Broccoli and its active ingredient, sulforaphane were reported to possess tremendous pharmacological activities such as anticancer, antimicrobial, antidepressant, antihypertensive and antidiabetic to mention but few. Here in, the antidiabetic potential of broccoli and sulforaphane (clinical trials, in vivo and in vitro models) were critically reviewed and discussed. Methods: Relevant articles were sourced from the major scientific databases (Scopus, PubMed, and Google Scholar). Results: Collectively, the data revealed that broccoli and sulforaphane have the potential to reduce hyperglycemia, hyperlipidemia, insulin resistance and diabetes-induced oxidative stress. Such activities were linked to but not limited to the activation of Nrf2 and PI3K/Akt pathways, inhibitions of NF-κB, GSK3β, α-glucosidase and DPP-IV activities. Conclusion: With the current available clinical evidence, broccoli and sulforaphane are regarded as adjuncts in diabetes treatment but not classical antidiabetic drugs. Further detail clinical trials are warranted especially the phases II and III, where large number of diabetic patients will be recruited. In addition, improving bioavailability while improving efficacy and reducing toxicity are of paramount.